Edukasi Dan Pelatihan Senam Kaki Diabetes Pada Kader Dalam Upaya Pencegahan Penyakit Diabetes di Wilayah Kerja Puskesmas Sengeti - La Ode Reskiaddin; M. Ridwan; Vinna Rahayu Ningsih (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Non-Communicable Diseases (NCD) is still quite high at the Sengeti Health Center. This is due to an unhealthy diet. The habit of people consuming high fat and sweet foods and the lack of community participation in the use of integrated service posts (posbindu). Efforts that can be made to overcome these problems are through education and training of cadres to do diabetic foot exercises. This community service was carried out at the Sengeti Health Center as many as 12 health cadres from each work area. This service activity was carried out by 3 lecturers and 5 students. The results showed that there was a difference in the mean knowledge of cadres from before (8.83 ± 0.937) and after education (9.92 ± 0.289) with a difference value of -4.168. In addition, there was an increase in skills both during training and after training. The need for monitoring and follow-up activities in the community.